Pengaruh CO2 Emmision, Cash Holding dan Leverage Terhadap Keputusan Investasi pada Sektor Pertambangan di Indonesia - Farhan Akmal Nuryadin; M. Amin Kadafi; Margareth Henrika (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the effect of CO₂ Emissions, Cash Holding, and Leverage on investment decisions in mining sector companies in Indonesia. This research employs a quantitative approach using secondary data obtained from the financial statements of companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The sampling technique used is purposive sampling. The data analysis method applied is panel data regression with a Fixed Effect Model. The results show that partially, CO₂ Emissions and Leverage do not have a significant effect on investment decisions, while Cash Holding has a negative and significant effect on investment decisions. This indicates that companies tend to retain cash as a precautionary measure against uncertainty, thereby reducing investment realization. Simultaneously, all independent variables have a significant effect on investment decisions. These findings suggest that internal financial factors remain the primary consideration compared to environmental factors in investment decision-making within the mining sector in Indonesia. This study is expected to contribute to the existing literature and provide insights for management and investors in determining optimal investment strategies.